La0.8Sr0.2Ga0.8Mg0.2O3 electrolytes prepared by vacuum cold spray under heated gas for improved performance of SOFCs. Issue 12 (15th August 2018) - Wang, Li-Shuang; Li, Cheng-Xin; Ma, Kai; Zhang, Shan-Lin; Yang, Guan-Jun; Li, Chang-Jiu
Abstract: High impact velocity of particles has found its common way into the vacuum cold spray (VCS), but heating gas may further intensify this function, resulting in significantly higher impact velocity. That's the original design idea to realize denser ceramic deposition at low temperature in this paper. In this study, a ~ 10 µm thick La0.8 Sr0.2 Ga0.8 Mg0.2 O3 (LSGM) electrolyte layer for SOFCs is prepared by VCS under heated gas. The effects of gas temperature on the deposition behavior, mechanical and electrical properties of the coatings are investigated. Results show improvements in coating density, hardness and ionic conductivity at elevated temperature. Additionally, the output performance of cell with LSGM electrolytes deposited at gas temperature of 400 °C achieved an open circuit voltage of ~ 1.0 V and the maximum power density of 855 mW/cm 2 at 750 °C. Overall, these findings testify of the promising aspects of VCS method for preparing solid electrolyte films for IT-SOFCs.